The Influence of Influencer Credibility, Posting Frequency, and Entertainment Value on Social Media Engagement Behavior of Culinary Products - Hendra, Hendra; Hendratni, Tyahya Whisnu; Istiqomah, Yuliani; Putrianti, Flora Grace; Mundzir, Mundzir; Bait, Jennifer Farihatul (Journal of Social Science and Business Studies, 2025)
This research aims at identifying the role of social media influencers' credibility, the frequency of posts, and the entertainment value of posts in consumer engagement behavior to culinary products on social media channels. Quantitative explanatory research method has been utilized whereby 300 people who are social media active users and frequently involved with culinary content were given a questionnaire. Purposive sampling was applied in this research basing it on the online behavior of the respondents, and the data was analyzed using multiple linear regression. The findings indicated that influencer's credibility, posting frequency, and content's entertainment value, all three independent variables were positively and significantly correlated with engagement behavior in social media. The present study not only contributes to the development of the theory of digital marketing and consumer behavior but also provides practical recommendations to culinary marketers on how to develop and maintain engagement strategies that are credible, consistent, and entertaining.